Investigating the Impact of Oil Prices Changes on Financial Market Efficiency in Saudi Arabia for the Period (1980-2018): ARDL Approach - Alhakimi, Saif Sallam; Sharaf-Addin, Hussein Hussein Hamood (International Journal of Energy Economics and Policy, 2022)
The impact of macroeconomic variables on the financial market efficiency has been a hot topic for decades. Thus, this study investigates the effect of oil price changes on the financial market performance using the estimation of Auto-Regressive Distributed Lag (ARDL) technique in Saudi Arabia for the period 1980-2018. The results revealed a long-run causality between the exchange rate, return on investment, and oil prices towards the financial market efficiency. However, only inflation and return on investment have causality effects on financial market efficiency in the short run. In addition, the exchange rate and oil price do not have causality running to economic market efficiency. Thus, both the short-run and long-run causality effects should be considered as guidelines to be followed by policymakers to avoid any misleading macroeconomic strategies in future strategic planning. The speed of adjustment reported from estimating the Conditional Error Correction Regression is (-0.114527). Also, the model was found stable from using both the CUSUM and CUSUMQ statistics.